A comparative mechanical and biocompatibility study of poly(ε-caprolactone), hybrid poly(ε-caprolactone)–silk, and silk nanofibers by colloidal electrospinning technique for tissue engineering. (September 2014) - Sheikh, Faheem A; Ju, Hyung Woo; Moon, Bo Mi; Park, Hyun Jung; Kim, Jung-Ho; Kim, Soo Hyeon; Lee, Ok Joo; Park, Chan Hum
Poly(ε-caprolactone) is an established polymer used in the fabrication of scaffolds for tissue engineering applications. Poly(ε-caprolactone)'s intrinsic hydrophobicity and toxicity, however, is greater than other natural polymers which limits its applicability. In this study, these problems were addressed by the modification of poly(ε-caprolactone) nanofibers with nanoparticles made from natural polymers, such as silk fibroin. Silk fibroin nanoparticles were prepared by desolvation and blended with poly(ε-caprolactone) to form a colloidal solution capable of forming nanofibers by electrospinning. Fabricated silk fibroin nanoparticles and three different nanofibers were characterized by transmission electron microscopy, variable pressure field emission scanning electron microscope, contact angle, Fourier transform infrared spectroscopy, thermogravimetric analysis, as well as an evaluation of their mechanical properties. The hybrid nanofibers incorporated with silk nanoparticles improved water absorbability compared to pure poly(ε-caprolactone) nanofibers and had much better mechanical properties than the silk fibroin nanofibers. The cytotoxicity and cell attachment tests were carried by culturing NIH 3T3 fibroblasts with the nanofibers. The hybrid nanofibers exhibited better cell viability and cell attachment than the pure poly(ε-caprolactone) nanofibers. Furthermore, the silk fibroin nanoparticles improved the water contact angle and enhanced cell interaction compared to the unmodified poly(ε-caprolactone). Based on these results, the modification of poly(ε-caprolactone) nanofibers with silk nanoparticles is a promising strategy for the improvement of poly(ε-caprolactone)-based nanofibers for future tissue engineering applications.